Interfacial Influence of Strontium Niobium Engulfed Reduced Graphene Oxide Composite for Sulfamethazine Detection: Employing an Electrochemical Route in Real Samples. Issue 5 (18th May 2021) - Nataraj, Nandini; Chen, Shen-Ming
Abstract : Sulfonamides are a broad assortment of drugs utilized in treating bacterial diseases in veterinary and human existence as anti-infection agents. The escalating usage of such medications requires explicit recognition. This work describes the electrochemical detection of sulfamethazine (SMZ) (a subgroup of sulfonamides) using strontium niobium combined with reduced graphene oxide (SN/rGO) as composite material. The structural and topological criteria illustrate the surface immaculateness and elemental presence of the crystalline material SN/rGO with XRD and FE-SEM analysis. Additional examinations of chemical states and the functional group were identified with XPS and FT-IR measurements. The feasibility of the sensor was inspected in the record of electrochemical studies. Electrochemical impedance spectroscopy (EIS) and cyclic voltammetry (CV) studies have demonstrated the effective implementation of the fabricated sensor with facilitating higher electroactive sites and enhanced conductance with SN/rGO. The amalgamation of SN and rGO has substantial influence with a lower limit of detection 6 nM with linearity from 0.009 μ M to 128 μ M. The limit of quantification was about 0.0224 μ M. The specific detection acquired over anti-interference studies and real-world actualize over milk, honey, and human blood serum tests mirror SN/rGO modified platform's viable capability. The construction of SN/rGO is envisioned as a promising dais for improved SMZ sensing in real samples.